Perbandingan Tampilan Estrus Sapi Bali Secara Alamiah dan Hasil Induksi Prostaglandin F2α - Gue, Febronia Dhenge; Hine, Thomas Mata; Uly, Kirenius (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this research is to examine the performance comparison of the estrous apperance of bali cattle naturally with those induced by protaglandin F2α. this study used 32 non-pregnant and healthy bali cattle. The sap criteria used were aged 3-15 years, had a body weight of 240-389 kg. The cattle used had a body condition score of 3-4 (medium and fat). The cattle were divided inti two groups, group 1 synchronized with PGF2α as much as 500 mg/ml intramuscularly, and group 2 was not injected with PGF2α. The study was designed using a completely randomized design. The research data was tabulated and analyzed using the T-test. The results analysis estrous onset, duration of estrous, estrous intensity and percentage of estrous respectively in treatment group 1 vs. 2 for the group were 80,13 hours; 10,55 vs 10,64 hours, 2,00 vs 2,69 hours, 90,47 vs 100%. The bottom line is that there is no difference in appearance of estrous between bali cattle induced with PGF2 alpha and those without (natural estrous).